SPR Characteristics Curve and Distribution of Residual Stress in Self-Piercing Riveted Joints of Steel Sheets. (15th February 2017) - Haque, Rezwanul; Wong, Yat C.; Paradowska, Anna; Blacket, Stuart; Durandet, Yvonne
Abstract : Neutron diffraction was used to describe the residual stress distributions in self-piercing riveted (SPR) joints. The sheet material displayed a compressive residual stress near the joint, and the stress gradually became tensile in the sheet material far away from the joint. The stress in the rivet leg was lower in the thick joint of the softer steel sheet than in the thin joint of the harder steel sheet. This lower magnitude was attributed to the lower force gradient during the rivet flaring stage of the SPR process curve. This study shows how the residual stress results may be related to the physical occurrences that happened during joining, using the characteristics curve. The study also shows that neutron diffraction technique enabled a crack in the rivet tip to be detected which was not apparent from a cross-section.